Analisis Gaya Bahasa dalam Geguritan Udan Kapang sebagai Alternatif Bahan Ajar Sastra di SMA - Shanti Rochmatin; Lulus Irawati; Dwi Rohman Soleh (Universitas PGRI Madiun, 2023)
Abstract: This study is focused on analyzing the language style in the Geguritan Udan Kapang Anthology and the language style used as teaching materials for high school literature. The object of the research is the language style and language style used as teaching materials in the anthology Geguritan Udan Kapang. The instrument used in this research is the researcher himself and is assisted by books that become study material or refer to. Test the validity of the data in this study is to use semantic validity and credibility to increase persistence. The data collection technique used by the writer is library technique and note-taking technique. The type of research used in this research is descriptive qualitative research. The technique of presenting the results of data analysis used by the author is an informal technique. This study uses a descriptive method. The results and discussion of the data show that the style of language contained in the anthology of Geguritan Udan Kapang found 16 language styles. This research can be used as teaching material for high school literature